2019
DOI: 10.1111/jdv.15767
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo confocal laser scanning microscopy for bullous pemphigoid diagnostics: new era in direct immunofluorescence?

Abstract: Background Ex vivo confocal laser scanning microscopy (ex vivo CLSM) is a novel diagnostic method allowing rapid, high‐resolution imaging of excised skin samples. Furthermore, fluorescent detection is possible using fluorescent‐labelled antibodies. Objective To assess the applicability of ex vivo CLSM in the detection of basement membrane (BM) fluorescence in bullous pemphigoid (BP) and to compare its diagnostic accuracy with direct immunofluorescence (DIF) microscopy. Methods A total of 81 sections of 49 BP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
0
27
0
3
Order By: Relevance
“…Different staining methods have been used to enhance the contrast of cell structures in ex vivo CM with no damage to conventional histopathology preparation (Table 3). 14,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Correlation of ex vivo confocal microscopy and normal skin histology Ex vivo confocal images allow a good correlation with conventional histology with H&E ( Figure 2). In a recent study by Sch€ u€ urmann et al, 38 using the VivaScope V2500, they found that the following cutaneous and subcutaneous structures are excellently displayed in the images, with only minimal differences compared with H&E slides: every layer of the epidermis, collagen and elastic tissue; lymphatic and capillary vessels; hair follicles and other skin appendages; eccrine and sebaceous glands; subcutaneous fat; elastic cartilage and muscle fibres.…”
Section: Technologymentioning
confidence: 99%
“…Different staining methods have been used to enhance the contrast of cell structures in ex vivo CM with no damage to conventional histopathology preparation (Table 3). 14,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Correlation of ex vivo confocal microscopy and normal skin histology Ex vivo confocal images allow a good correlation with conventional histology with H&E ( Figure 2). In a recent study by Sch€ u€ urmann et al, 38 using the VivaScope V2500, they found that the following cutaneous and subcutaneous structures are excellently displayed in the images, with only minimal differences compared with H&E slides: every layer of the epidermis, collagen and elastic tissue; lymphatic and capillary vessels; hair follicles and other skin appendages; eccrine and sebaceous glands; subcutaneous fat; elastic cartilage and muscle fibres.…”
Section: Technologymentioning
confidence: 99%
“…Ex vivo CLSM is a relatively new diagnostic method that has been established in dermatology in the last few years. Only recently, the possibility of using FITC (fluorescein isothiocyanate)-labeled antibodies in ex vivo CLSM was firstly described in two pilot studies (12, 14). The images presented in our case present one of the first applications of FITC-labeled antibodies in ex vivo confocal CLSM.…”
Section: Discussionmentioning
confidence: 99%
“…An innovative examination method, the ex vivo confocal laser scanning microscopy (CLSM), offers an ultra-rapid vertical scanning of skin samples with a resolution close to conventional histology and a possibility to apply immunofluorescent dyes and specific antibodies (1215). In addition, the ex vivo CLSM is faster than using DIF, which was previously established as the gold standard when performing immunostaining (14). We present the ex vivo CLSM examination results in our patient as a possible alternative to DIF ( Figures 2E–H ).…”
Section: Introductionmentioning
confidence: 99%
“…Ähnliche Ergebnisse konnten bei der Bewertung der Anwendbarkeit von ex vivo KLM beim Nachweis der Basalmembran-Fluoreszenz beim bullösen Pemphigoid (BP) erzielt werden [18]. Hier zeigte sich eine Gesamtleistung von 65,3 % bei der Identifizierung der Basalmembran-Fluoreszenz bei BP-Patienten.…”
Section: Bullöses Pemphigoidunclassified
“…Die Sensitivität der ex vivo KLM beim Nachweis der Basalmembran-Fluoreszenz war gering (IgG: 50 %, C3: 45,5 %), aber die Spezifität war hoch (IgG: 100, C3: 90 %). Ex vivo KLM konnte neben der Immunreaktivität bei 84 % der Patienten subepidermale Entzündungszellen ähnlich zu der histologischen Untersuchung nachweisen [18].…”
Section: Bullöses Pemphigoidunclassified